Do future healthcare professionals advocate for pharmacogenomics? A study on medical and health sciences undergraduate students - Al-Suhail, Hanan; Omar, Mohammad; Rubaeih, Majd; Mubarak, Tamer; Koufaki, Margarita-Ioanna; Kanaris, Ioannis; Mounaged, Favio; Patrinos, George P.; Saber-Ayad, Maha (Frontiers in Pharmacology, 2024)
Pharmacogenomics (PGx) is a rapidly changing field of genomics in which healthcare professionals play an important role infor its implementation in the clinical setting, however PGx level of adoption remains low. This study aims to investigate the attitude, self-confidence, level of knowledge, and their impact on health sciences undergraduate students' intentions to adopt PGx in clinical practice using a questionnaire developed based on the Theory of Planned Behavior (TPB). A model was proposed and a questionnaire was developed that was distributed to 467 undergraduate students of all academic years from four different departments of the University of Sharjah (UoS) including medical, dental, nursing, and pharmacy students duringfrom September 2022 to November 2022. Descriptive statistics along with factor analysis and regression analysis were conducted. The proposed model had a good internal consistency and fit. Attitude was the factor with the greatest impact on student's intentions followinged by self-confidence and barriers. LThe level of knowledge had a meaningless impact. The majority of students shared a positive attitude and were aware of PGx benefits. Almost 60% of the respondents showed a high level of knowledge, while 50% of them were confident of implementing PGx in their clinical practice. Many students were prone to adopt PGx in their future careers. PGx testing cost and the lack of reimbursement were the most important barriers.Overall, students shared a positive intention and were prone to adopt PGx. In the future, it would be important to investigate the differences between gender, year of studies, and area of studies studies and their impact on students' intentions.